If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6 + -1v)(3v + -4) = 0 Reorder the terms: (6 + -1v)(-4 + 3v) = 0 Multiply (6 + -1v) * (-4 + 3v) (6(-4 + 3v) + -1v * (-4 + 3v)) = 0 ((-4 * 6 + 3v * 6) + -1v * (-4 + 3v)) = 0 ((-24 + 18v) + -1v * (-4 + 3v)) = 0 (-24 + 18v + (-4 * -1v + 3v * -1v)) = 0 (-24 + 18v + (4v + -3v2)) = 0 Combine like terms: 18v + 4v = 22v (-24 + 22v + -3v2) = 0 Solving -24 + 22v + -3v2 = 0 Solving for variable 'v'. Factor a trinomial. (-6 + v)(4 + -3v) = 0Subproblem 1
Set the factor '(-6 + v)' equal to zero and attempt to solve: Simplifying -6 + v = 0 Solving -6 + v = 0 Move all terms containing v to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + v = 0 + 6 Combine like terms: -6 + 6 = 0 0 + v = 0 + 6 v = 0 + 6 Combine like terms: 0 + 6 = 6 v = 6 Simplifying v = 6Subproblem 2
Set the factor '(4 + -3v)' equal to zero and attempt to solve: Simplifying 4 + -3v = 0 Solving 4 + -3v = 0 Move all terms containing v to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -3v = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -3v = 0 + -4 -3v = 0 + -4 Combine like terms: 0 + -4 = -4 -3v = -4 Divide each side by '-3'. v = 1.333333333 Simplifying v = 1.333333333Solution
v = {6, 1.333333333}
| x=2600 | | x-.2=13000 | | x*x=5 | | 4x+1=25-2x | | 15o^2+36o+17=0 | | ln(3x)=5.82 | | y^2+-3y+-40=0 | | 4.9(x+5.1)=36.8 | | -6n=54 | | -9+n=-8 | | 11x-2=3x+11 | | o^2+0o+-4=0 | | -7=p-5 | | 6s^2+3s=0 | | 802.1-4.82+9= | | y-9=-19 | | 4r^2+30r+10=0 | | 24=4n | | 8(x+12)-288=3x | | 3q+4=2q+10 | | 2x^2+8x=192 | | 8x+35=6x+27 | | n^2+-3n+-40=0 | | 7x+1=52 | | 10v^2-21v-49=0 | | 2x^3+8x^2-64=0 | | n^2+2n+-24=0 | | -2(x+3)-2(-x+3)=6-x | | -4(-2)-4y=4 | | 7-3r=r-4(2-r) | | 0=4x^3-256x | | 4(3X)=158 |